2020
DOI: 10.2471/blt.20.260281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 related knowledge, attitudes, practices and needs of households in informal settlements in Nairobi, Kenya

Abstract: DISCLAIMER This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
140
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 31 publications
29
140
6
2
Order By: Relevance
“…Our survey shows that 31% of the youth (1 in every 3) perceive themselves as being at low or no risk of getting infected with COVID-19. These levels varied with a previous study conducted in the informal settlement of Nairobi where about a third of participants felt they were at high risk of infection [22]. The low risk was associated with having no history of travel and the believe that God will protect them.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our survey shows that 31% of the youth (1 in every 3) perceive themselves as being at low or no risk of getting infected with COVID-19. These levels varied with a previous study conducted in the informal settlement of Nairobi where about a third of participants felt they were at high risk of infection [22]. The low risk was associated with having no history of travel and the believe that God will protect them.…”
Section: Discussionmentioning
confidence: 85%
“…The few who were not practicing such behaviors reported lack of water or soap, cost of masks and discomfort while wearing mask and costs of sanitizers as deterrent to practicing preventive behaviors. A previous survey conducted two weeks prior to this, showed that households are already performing risk reduction behaviors including increased hand washing with soap where possible, use of hand sanitizer, and staying home more [22]. Although these behaviors are practiced, additional focus should be how to sustain these behaviors on hygiene and social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Malaysia [19] to examine knowledge, perception and communication behaviour among publics in Malaysia showed that the level of knowledge, risk perceptions and positive communication behaviour related to COVID-19 was high, where the majority of the respondents correctly answered knowledge related questions, perceived the risks and impacts of COVID-19 seriously. Likewise, a similar study in Kenya in informal settlements [20] showed knowledge regarding COVID-19 symptoms and highrisk groups were accurate however some misconceptions remained regarding speci c symptoms and considering children as high-risk groups. Another study conducted in Egypt to assess the knowledge, perceptions, and attitude of the public towards the disease showed that the participants had good knowledge and positive attitude towards the protective measures against COVID-19, which was mainly gained through social media and the internet.…”
Section: Discussionmentioning
confidence: 88%
“…Only 2597(72.4%) participants knew that there is currently no available treatment; this is higher than a Kenyan study (40%) but signi cantly lower than a Chinese study (94%). (12,15) A minority 103(2.9%) participants thought there was a vaccine available against COVID-19; by contrast, Coimbatore District (18.6%) and Pakistan (11.6%) were misinformed. In the absence of a vaccine or effective treatment protocol for COVID-19, controlling the spread of the disease is the best line of defense.…”
Section: Discussionmentioning
confidence: 99%
“…(6,11) While some studies have been conducted to assess the knowledge, attitude, and practices among populations during this pandemic, none have done so in Syria. (12)(13)(14)(15)(16)(17)(18)(19) To our knowledge this rst study that aims to measure the awareness and general knowledge of COVID-19 among the Syrian population at a time where ambiguity and misinformation are rampant. The objective of this study is to gauge speci c knowledge around clinical features, transmission pathways, and prevention methods, and to identify factors associated with poor knowledge to help facilitate outbreak management in Syria during this rapid global rise of the COVID-19 pandemic.…”
mentioning
confidence: 99%